Analysis of the Imposition of Entry Stamps on the Crew of Transportation Equipment against Permenkumham Number 44 of 2015 - Rafly Mardiyanto; Muhammad Luthfi; Nur Aini (IHSA Institute, 2022)
Migration of people has occurred from prehistoric times where humans at that time (ancient humans) lived in a nomadic way or moved from one place to another. However, in prehistoric times there were no countries and no known borders between countries so that humans were very free to move. In this modern era, humans also move from one place to another, both within the scope of Regency/City, Province, Island, and even State. Every country has an area where between each region of the country a boundary must be determined. The concept of territorial boundaries is divided into 3 (three) namely Border, Frontier, and Boundrie. Of the three concepts, Immigration as the agency that first welcomes everyone who enters the territory of Indonesia and as the agency that is last met before leaving the territory of Indonesia is at the Immigration Checkpoint. In passing the Immigration Checkpoint, one must have clear requirements and goals so that later they can be given a stamp as an entry permit into Indonesian territory. The Entry Stamp is a sign given by the Immigration officer at the Immigration Checkpoint as a sign that someone is allowed to enter the Indonesian Territory.